One x, two x, three x

Geometry Level 3

If sin x = 13 cos x \sin {x} = -13\cos{x} . Then, the value of

sin x + sin 2 x + sin 3 x cos x + cos 2 x + cos 3 x \begin{aligned} \frac{\sin {x} + \sin{2x} + \sin{3x}}{\cos{x}+\cos{2x}+\cos{3x}} \end{aligned}

can be expressed in the form a b \frac{a}{b} , where a a and b b are positive coprime integers. What is the value of a + b a+b ?


The answer is 97.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

9 solutions

Andrew Ong
Dec 25, 2013

sin x = 13 cos x sin x cos x = tan x = 13 sin x + sin 2 x + sin 3 x cos x + cos 2 x + cos 3 x = ( sin 3 x + sin x ) + sin 2 x ( cos 3 x + cos x ) + cos 2 x = 2 sin 2 x cos x + sin 2 x 2 cos 2 x cos x + cos 2 x = sin 2 x ( 2 cos x + 1 ) cos 2 x ( 2 cos x + 1 ) = tan 2 x = 2 tan x 1 tan 2 x = 2 ( 13 ) 1 ( 13 ) 2 = 13 84 \sin x = -13\cos x \Rightarrow \frac{\displaystyle \sin x}{\displaystyle \cos x} = \tan x = -13 \\ \frac{\displaystyle \sin x + \sin 2x + \sin 3x}{\displaystyle \cos x + \cos 2x + \cos 3x} \\ = \frac{\displaystyle (\sin 3x + \sin x) + \sin 2x}{\displaystyle (\cos3x + \cos x) + \cos 2x} \\ = \frac{\displaystyle 2\sin 2x\cos x + \sin 2x}{\displaystyle 2\cos 2x\cos x + \cos 2x} \\ = \frac{\displaystyle \sin2x(2\cos x + 1)}{\displaystyle \cos2x(2\cos x + 1)} \\ = \tan 2x \\ = \frac{\displaystyle 2\tan x}{\displaystyle 1-\tan^2 x} = \frac{\displaystyle 2 \cdot (-13)}{\displaystyle 1 - (-13)^2} = \boxed{\frac{\displaystyle 13}{\displaystyle 84}}

From 2nd to 3rd line, we use the sum-to-product identities cos A + cos B = 2 cos A + B 2 cos A B 2 \cos A + \cos B = 2\cos \frac{\displaystyle A+B}{\displaystyle 2} \cos \frac{\displaystyle A-B}{\displaystyle 2} and sin A + sin B = 2 sin A + B 2 cos A B 2 \sin A + \sin B = 2\sin \frac{\displaystyle A+B}{\displaystyle 2} \cos \frac{\displaystyle A-B}{\displaystyle 2}

Andrew Ong - 7 years, 5 months ago

Awesome solution :D

Mohamed Abdelaaty - 7 years, 5 months ago

exactly same way..i did

Deepak Kumar - 7 years, 5 months ago

This problem can be solved by using the basic trigonometric formulae. sin x + sin 2 x + sin 3 x cos x + cos 2 x + cos 3 x \frac{\sin x+\sin 2x +\sin 3x}{\cos x+\cos 2x +\cos 3x} = ( sin x + sin 3 x ) + sin 2 x ( cos x + cos 3 x ) + cos 2 x =\frac{(\sin x+\sin 3x) +\sin 2x}{(\cos x+\cos 3x) +\cos 2x} = 2 sin ( x + 3 x 2 ) cos ( x 3 x 2 ) + sin 2 x 2 cos ( x + 3 x 2 ) cos ( x 3 x 2 ) + cos 2 x =\frac{2\sin(\frac{x+3x}{2}) \cos(\frac{x-3x}{2})+\sin 2x}{2\cos(\frac{x+3x}{2}) \cos(\frac{x-3x}{2})+\cos2x} = 2 sin ( 4 x 2 ) cos ( 2 x 2 ) + sin 2 x 2 cos ( 4 x 2 ) cos ( 2 x 2 ) + cos 2 x =\frac{2\sin(\frac{4x}{2}) \cos(\frac{-2x}{2})+\sin 2x}{2\cos(\frac{4x}{2}) \cos(\frac{-2x}{2})+\cos2x} = 2 ( sin 2 x ) ( cos ( x ) ) + sin 2 x 2 ( cos 2 x ) ( cos ( x ) ) + cos 2 x =\frac{2(\sin 2x)(\cos (-x))+\sin 2x}{2(\cos 2x)(\cos (-x))+\cos 2x} = sin 2 x ( 2 cos ( x ) + 1 ) cos 2 x ( 2 cos ( x ) + 1 ) =\frac{\sin 2x(2\cos (-x)+1)}{\cos 2x(2\cos (-x)+1)} = sin 2 x cos 2 x =\frac{\sin 2x}{\cos 2x} = tan 2 x =\tan 2x = 2 tan x 1 tan 2 x =\frac{2\tan x}{1-\tan^{2}x} = 2 sin x cos x 1 sin 2 x cos 2 x =\frac{2\frac{\sin x}{\cos x}}{1-\frac{\sin^{2}x}{\cos^{2}x}} Now substitutins sin x = 13 cos x \sin x=-13\cos x ,we get = 2 × 13 1 ( 13 ) 2 =\frac{2 \times -13}{1-(-13)^{2}} = 26 1 169 =\frac{-26}{1-169} = 26 168 =\frac{-26}{-168} = 13 84 =\frac{13}{84} Now, a b = 13 84 \frac{a}{b}=\frac{13}{84} a + b = 13 + 84 \Rightarrow a+b=13+84 a + b = 97 \Rightarrow a+b=97 Therefore, the answer to this question is 97 \boxed{97} .

tan x = sin x cos x \tan x=\frac{\sin x}{\cos x} tan x = 13 cos x cos x \Rightarrow \tan x=\frac{-13\cos x}{\cos x} tan x = 13 \Rightarrow \tan x=-13

Soham Dibyachintan - 7 years, 5 months ago
Luca Bernardelli
Dec 24, 2013

sin x + sin 2 x + sin 3 x cos x + cos 2 x + cos 3 x = sin x + 2 sin x cos x + sin x ( 2 cos 2 x + 1 ) cos x + 2 cos 2 x 1 + cos x ( 2 cos 2 x 1 ) = \cfrac{ \sin x + \sin 2x + \sin 3x }{\cos x + \cos 2x + \cos 3x} = \cfrac{ \sin x + 2 \sin x \cos x + \sin x (2\cos 2x +1) }{\cos x + 2\cos ^2 x -1 + \cos x (2 \cos 2x -1) } =

sin x ( 1 + 2 cos x + 2 cos 2 x + 1 ) cos x + 2 cos 2 x 1 + 2 cos x cos 2 x cos x = 2 sin x ( 1 + cos x + cos 2 x ) 2 cos 2 x 1 + 2 cos x cos 2 x = \cfrac{ \sin x (1 + 2\cos x + 2\cos 2x +1) }{\cos x + 2\cos ^2 x -1 + 2 \cos x \cos 2x -\cos x } = \cfrac{ 2\sin x (1 + \cos x + \cos 2x) }{2\cos ^2 x -1 + 2 \cos x \cos 2x } =

2 sin x ( 1 + cos x + 2 cos 2 x 1 ) cos 2 x + 2 cos x cos 2 x = 2 sin x ( cos x + 2 cos 2 x ) cos 2 x ( 1 + 2 cos x ) = \cfrac{ 2\sin x (1 + \cos x + 2\cos ^2 x -1) }{\cos 2x + 2 \cos x \cos 2x } = \cfrac{ 2\sin x (\cos x + 2\cos ^2 x ) }{\cos 2x (1 + 2 \cos x) } =

2 sin x cos x ( 1 + 2 cos x ) cos 2 x ( 1 + 2 cos x ) = 2 sin x cos x cos 2 x = sin 2 x cos 2 x = tan 2 x \cfrac{ 2\sin x \cos x (1 + 2\cos x) }{\cos 2x (1 + 2 \cos x) } = \cfrac{ 2\sin x \cos x }{\cos 2x } = \cfrac{ \sin 2x }{\cos 2x } = \tan 2x

tan 2 x = 2 tan x 1 tan 2 x \tan 2x = \cfrac {2\tan x}{1- \tan^2 x}

We know that sin x = 13 cos x tan x = 13 \sin x = -13\cos x \Rightarrow \tan x = -13

2 tan x 1 tan 2 x = 26 1 1 3 2 = 26 168 = 13 84 \cfrac {2\tan x}{1- \tan^2 x} = \cfrac {-26}{1- 13^2} = \cfrac {26}{168} = \cfrac {13}{84}

Solution is 13 + 84 = 97 13+84 = \boxed{97} .

Puja Shree
Dec 24, 2013

numerator : sinx+sin2x+sin3x

by the formula - sinx+siny= sin(x+y)/2 cos(x-y)/2 { cos(-x)=cosx } for sinx+sin3x we get, 2sin2xcosx

so sin2x + 2sin2xcosx = sin2x(1+cosx)

Denominator : cosx+cos2x+cos3x

by the formula , cosx + cosy = 2cos(x+y)/2cos(x-y)/2 { cos(-x)=cosx } cosx+cos3x= 2cos2xcosx

cos2x+ 2cos2xcosx = cos2x(1+cosx)

now NR/ DR = sin2x(1+cosx)/cos2x(1+cosx)

we get , tan2x

WKT - tan2x= tanx/1-tan^2x

tanx = sinx/cosx

sinx=-13cosx (GVN)

there fore

tanx = -13 and Tan^2x = 169

substituting in tan2x we get 13/94 = a/b

there fore a+b = 97 (ANS)

Diamantis Koreas
Dec 27, 2013

We know that: sin(a+b)=sin(a) cos(b) +sin(b) cos(a) and cos(a+b)= cos(a) cos(b)-sin(a) sin(b). Since sin(-a) =-sin(a) and cos(-a)=cos(a) we also get: sin(a-b)=sin(a) cos(b) -sin(b) cos(a) and cos(a-b)= cos(a) cos(b)+sin(a) sin(b). Combing these inequalities we get that: sin(A) + sin(B) = 2* sin((A+B)/2)* cos((A-B)/2) and cos(A) + cos(B) = 2* cos((A+B)/2)* cos((A-B)/2), where A=a+b and B=a-b. So, sin(x) + sin(3x)= 2 sin(2x) cos(x) and sin(x)+sin(2x) +sin(3x)=(2 cos(x) +1) sin(2x). Also cos(x)+cos(3x)=2 cos(2x) cos(x) and cos(x) +cos(2x)+cos(3x)=(2 cos(x) +1) cos(2x). Finaly we get: sin(2x)/cos(2x) = (2 sin(x) cos(x)) / (cos(x)^2 -sin(x)^2) = -26*cos(x)^2/-168cos(x)^2 =26/168 = 13/84.

Azizul Islam
Dec 25, 2013

sin 2x (1+cos 2x)/cos 2x (1+cos 2x) = tan 2x = 2(-13)/(1-(-13)^2) = 13/84 = 97

Please explain the steps.

Soham Dibyachintan - 7 years, 5 months ago

Log in to reply

oops!! made a typing mistake, it'll be

sin 2x (1+2cos x)/cos 2x (1+2cos x) = tan 2x

here we go, sin 3x + sin x + sin 2x

= 2 sin (3x+x)/2 cos (3x-x)/2 + sin 2x

= 2 sin 2x cos x + sin 2x

= sin 2x (1+ 2 cos x)

cos 3x +cos x +cos 2x

= 2 cos (3x+x)/2 cos(3x-x)/2 + cos 2x

= 2 cos 2x cos x + cos 2x

= cos 2x (1+ 2 cos x)

Azizul Islam - 7 years, 5 months ago
Siddharth Shah
Dec 25, 2013

Combining the first and last terms of numerator and denominator, we get sinx + sin3x + sin2x / cosx + cos3x + cos2x using the formula for sinc + sind = 2sin((C+D)/2)cos((C-D)/2) and cosc + cosd = 2cos((C+D)/2)cos((C-D)/2) we get 2sin2xcosx + sin2x / 2cos2xcosx + cos2x = sin2x(2cosx +1) / cos2x(2cosx+1), which on cancellation gives sin2x/cos2x which is equal to tan2x. Now using the formula again for tan2x, we have tan2x= 2tanx/1-tan^2 x. From the question we have sinx=-13cosx which gives tanx = -13. Plugging the values for tanx in the obtained expression we have expr = 26/168 = 13/84. Hence the answer = 13 + 84 = 97 \boxed{97}

Ramiel To-ong
Dec 4, 2015

nice problem

Israel Smith
Dec 31, 2013

[sin(x)+sin(2x)+sin(3x)]/[cos(x)+cos(2x)+cos(3x)] = tan(2x). Notice that sin(x)=-13cos(x). tan(2x)=[2sin(x)cos(x)]/[cos^2(x)-sin^2(x)] tan(2x)=-26cos^2(x)/168cos^2(x)= 13/84 a=13 and b=84, a+b=97

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...